2013
DOI: 10.1186/1752-1947-7-48
|View full text |Cite
|
Sign up to set email alerts
|

Consumptive hypothyroidism in an Egyptian baby with benign neonatal hemangiomatosis: a case report

Abstract: IntroductionBenign neonatal hemangiomatosis is a condition in which multiple cutaneous hemangiomas appear at birth or shortly thereafter; visceral complications are absent. Here, we report a case of a consumption hypothyroidism in an Egyptian baby with benign neonatal hemangiomatosis.Case presentationAn 8-month-old Egyptian boy with benign neonatal hemangiomatosis was referred to our institution for evaluation of developmental delay. Initial examination revealed a quiet baby who was able to sit only with suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The diagnosis of CHS requires a high suspicion index in patients with positive neonatal screening for hypothyroidism [6]. Of note, in our review, neonatal screening identified 32% (7/22) of CHS cases in children as congenital hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of CHS requires a high suspicion index in patients with positive neonatal screening for hypothyroidism [6]. Of note, in our review, neonatal screening identified 32% (7/22) of CHS cases in children as congenital hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in our review, neonatal screening identified 32% (7/22) of CHS cases in children as congenital hypothyroidism. Some characteristics can help to differentiate CHS from other forms of congenital hypothyroidism, namely, normal thyroid morphology and iodine incorporation, high levels of rT 3 and the requirement of high doses of LT 4 /LT 3 to restore serum TSH normal levels [6]. Notwithstanding, since hemangiomas are the most common vascular tumors in children, occurring in approximately 5–10% of 1-year-old children [7], it is reasonable to speculate that the actual prevalence of CHS may be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, two cases of consumptive hypothyroidism associated with cutaneous hemangioma have been reported in infants (40). Moreover, a case of neonatal hemangioma in the skin, associated with consumptive hypothyroidism, has been reported in an 8-month-old infant (46). The first case of consumptive hypothyroidism secondary to a large parotid hemangioma was reported in 2012 in a child with congenital hypothyroidism and hypoplastic thyroid gland (47).…”
Section: Other Conditions Associated With Elevated D3 Levelsmentioning
confidence: 99%